The emotional impact of liaison interpreting in asylum settings: Perceptions of Arabic-Spanish interpreters - Mahyub Rayaa, Bachir (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2023)
The emotional impact of liaison interpreting has attracted research attention for decades (cognitive processes involved in language interpreting, stress and emotions in interpreter performance). However, research on the Arabic-Spanish language combination is still scarce, which does not do justice to the high demand experienced for these languages in public services in Spain and Europe. This paper analyses the results of an anonymous survey (8 items) that probes the perception of 30 Arabic-Spanish interpreters in asylum settings about the emotional impact of their job.